Computational investigation of microstrip antennas and couplers - Chen, Ye (2017)
With the development of wireless local-area network, more and more applications relies on this frequency band, the 5.5 GHz. Antennas are essential elements of the communication system to provide the transmission and receive of the signal. Due to the Miniaturization and low profile, the microstrip antenna is widely employed in the wireless communication with small dimensions. Whereas the hybrid coupler is applied in the microwave system to provide the power division. It also can realized by microstrip line for small dimension comparing to those made of waveguide. The aim of this thesis is to design microstrip antennas and couplers at 5.5 GHz for wireless local-area network and investigate to connect these two kinds of devices. Due to the high flexibility in modelling, CST MICROWAVE STUDIO is employed during the whole process of design and simulation. Two antennas are designed at the resonant frequency of 5.5 GHz, the rectangular microstrip antenna possesses high directivity, whilst the copper coin shape antenna owns broad bandwidth. While two kinds of hybrid couplers are designed in different structure, the quadrature hybrid coupler and rat race ring. Finally the rectangular microstrip antenna is chosen to connect with the quadrature coupler with better division performance.